Interplay between metabolic identities in the intestinal crypt supports stem cell function - Rodríguez-Colman, Maria J.; Schewe, Matthias; Meerlo, Maaike; Stigter, Edwin; Gerrits, Johan; Pras-Raves, Mia; Sacchetti, Andrea; Hornsveld, Marten; Oost, Koen C.; Snippert, Hugo J.; Verhoeven-Duif, Nanda; Fodde, Riccardo; et al. (Nature (London), 2017)
The glycolytic activity of Paneth cells provides lactate, which is required by self-renewing intestinal stem cells for oxidative metabolism to activate p38 MAP kinase, ensuring regeneration of a mature crypt. Metabolism and gut regeneration Small intestine crypts are regenerated throughout life thanks to self-renewing stem cells located at the bottom of crypts. Differentiated Paneth cells provide the signalling molecules that modulate the regenerative properties of these stem cells. The influence of metabolism on the self-renewal of the crypt has not been studied in great detail. Burgering and colleagues now show that, whereas intestinal stem cells rely on mitochondrial activity for their metabolic needs, Paneth cells use glycolysis, a process that provides the lactate that is required by the stem cells for their oxidative metabolism. This activates the p38 MAP kinase to ensure regeneration of a mature crypt. The findings suggest that the metabolism of certain intestinal cells has an important role in supporting stem cell function. The small intestinal epithelium self-renews every four or five days. Intestinal stem cells (Lgr5 + crypt base columnar cells (CBCs)) sustain this renewal and reside between terminally differentiated Paneth cells at the bottom of the intestinal crypt 1 . Whereas the signalling requirements for maintaining stem cell function and crypt homeostasis have been well studied, little is known about how metabolism contributes to epithelial homeostasis. Here we show that freshly isolated Lgr5 + CBCs and Paneth cells from the mouse small intestine display different metabolic programs. Compared to Paneth cells, Lgr5 + CBCs display high mitochondrial activity. Inhibition of mitochondrial activity in Lgr5 + CBCs or inhibition of glycolysis in Paneth cells strongly affects stem cell function, as indicated by impaired organoid formation. In addition, Paneth cells support stem cell function by providing lactate to sustain the enhanced mitochondrial oxidative phosphorylation in the Lgr5 + CBCs. Mechanistically, we show that oxidative phosphorylation stimulates p38 MAPK activation by mitochondrial reactive oxygen species signalling, thereby establishing the mature crypt phenotype. Together, our results reveal a critical role for the metabolic identity of Lgr5 + CBCs and Paneth cells in supporting optimal stem cell function, and we identify mitochondria and reactive oxygen species signalling as a driving force of cellular differentiation.